Overseas cultural orientation programmes and resettled refugees’ perceptions - Julie M Kornfeld (Forced Migration Review, 2012)
Despite widespread participation in cultural orientation programmes, resettled refugees often have misconceptions about their potential for self-sufficiency in the United States, and experience adjustment problems after their arrival. Making changes to these programmes could improve outcomes of the refugee resettlement process.